Attempted altruistic infanticide in a context of psychotic decompensation induced by stress linked to the COVID-19pandemic: a case report - Camille Jantzi; Alexandre Perrin (Oxford University Press, 2021)
The mediatization of the COVID-19 pandemic has created a lot of stress leading sometimes to mental health issues. We present a case of a thirty-year-old woman with no history of psychotic disease but some vulnerabilities and no criminal record, who attempted to kill her seven-year-old son during a brief delusional episode in the context of fear of the coronavirus. She was successfully treated by pharmacotherapy and psychotherapy. She was examined by forensic psychiatrists leading to the conclusion that her responsibility was highly diminished, and her reoffending risk was low. We add to the literature that the COVID-19 pandemic has been such a stressor for mentally vulnerable people that it could lead to severe psychiatric decompensation and even criminal acts.